Application Of Nutrients In The Type Of Growing Media To The Yield Of Mustard Plants (Brasscia Juncea L.) Hydroponically Wick System - I Gusti Ngurah Aris Cakra Satria Wibawa; Made Sri Yuliartini; Anak Agung Ngurah Mayun Wirajaya (Warmadewa University Press, 2024)
The purpose of this study was to determine the effect of AB mix nutrient mixture with tofu pulp POC and type of growing media on the yield of mustard plants (Brassica juncea L.) hydroponically wick. This research was conducted from February to May 2023 in Kesiman Pentilan Village, East Denpasar, Denpasar City. The altitude is 20 meters above sea level, with a rainfall of 2,757 mm, the average temperature is 20-300C. This type of research is an experimental study using factorial Group Randomized Design (RAK) consisting of two factors. The first factor is a mixture of AB mix and liquid organic fertilizer (POC) which consists of 3 levels. The second factor is the type of media consisting of 3 levels. The first factor of AB Mix nutrition with tofu pulp POC consists of 3 levels, namely: (K1 AB mix + 20cc POC), K2 (AB mix + 30cc POC, (K3 AB mix + 40cc POC). Factors of both types of media consist of 3 levels, namely: M1 (rockwool), M2 (husk charcoal), M3 (cocopeat). So that 9 combination treatments were repeated 3 times so that there were 27 plants. Interaction between the dose of tofu pulp POC + AB mix with the type of growing media (KÃ—M); Tofu pulp POC dose treatment + AB mix (K) and type of growing medium (M) had no real effect (Pâ‰¥0.05) on all observed variables. The absence of interaction indicates that the combined treatment of nutrients and media types has not been able to affect plant physiological processes. Although the two treatment factors are not real for all variables observed, emperically from this study shows that the nutritional treatment of AB mix + 20cc POC tofu pulp with rockwool planting media. Shows the highest economic yield weight, namely 17.378 grams and 17.711 grams.